Influence of the thickness and absorption coefficient of a copper oxide film on the ignition delay of PENT by a laser pulse; Combustion, Explosion, and Shock Waves; Vol. 52, iss. 1 - Khaneft A. V. Aleksandr Villivich; Dolgachev V. A. Vadim Aleksandrovich; Zverev A. S. Anton Sergeevich; Mitrofanov A. Yu. Anatoliy Yuryevich (2016, 2016)
Title screen